art deco - Lidin, Konstantin (project baikal, 2019)
ART DECO is, probably, one of the most controversial and complex styles of the 20th century. The style is fine and, at the same time, vulgar. This style is a direct successor of the sophisticated art nouveau and the haughty kitsch of nouveaux riches. Being omnivorous, it has absorbed elements of almost all historical styles of East and West without staying within any stylistic limits… Probably, it is ART DECO which should be considered a precursor of the general stylistics of the 20th century. The selection of materials on the main topic of this issue is devoted to the thoughts on the ART Deco style, the style of brilliant designers and newly rich frauds.